If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 17u = 13u + 4 Reorder the terms: 17u = 4 + 13u Solving 17u = 4 + 13u Solving for variable 'u'. Move all terms containing u to the left, all other terms to the right. Add '-13u' to each side of the equation. 17u + -13u = 4 + 13u + -13u Combine like terms: 17u + -13u = 4u 4u = 4 + 13u + -13u Combine like terms: 13u + -13u = 0 4u = 4 + 0 4u = 4 Divide each side by '4'. u = 1 Simplifying u = 1
| 2+2x=-2 | | 0.8x-14.8=0.7x-6.7 | | 3x+5=3(x-5) | | 2t+25=t+38 | | 3.8x+5.2x=18 | | 5x-10+18=4x+16 | | 8x=11/3 | | 4y+27=y+37 | | 35=3u+14 | | 2x^2+2x=63 | | 3=-4x-17 | | (11x-45)+65+(9x-20)=180 | | 8n+3=3(2n-1) | | y=t^3-t-5 | | 4-7x=16+5x | | 2q/35=16-2/5q | | 4x+8=5(x+3) | | -x^3+4x^2+2x=0 | | l+(l+2)+l+(l+2)=30 | | a=b/d | | 21=6(x+2)-3 | | 2n-12=8(n+4) | | 2x=-3y-1 | | 3(5x+6)=-147 | | -10=-2x+2 | | 6a-20+3a=15+16 | | c=20h+35 | | x+9x+20= | | -13-4x-x=-3(5-9x)+2 | | 12n=17-19 | | 5(4+7x)=335 | | 3/7x-2/5=2 |